2021
DOI: 10.1186/s10086-021-01972-w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on partial compression parallel to grain of solid timber

Abstract: This paper describes results and analysis of experimental testing of entire and partial compression strength and stiffness parallel to the grain of solid timber (Japanese cedar). To investigate the spreading effects, the size effect of strength and stiffness, and the mechanism of the damage zone located close to the loading plates, tests on 90 specimens were performed. As a result, it was observed that damage zones existed near the loading plates. The observed spreading effects in the compression parallel to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The size effect of the cross-sectional area on the compressive strength f c,0 was very small. We have reported that there is no size effect in the f c,0 of the solid timber specimens [7]. The main reason of the strength reduction may be related to knots because the solid timber specimens did not have knots, whereas all the glulam specimens excluding the 2.5-1 specimens had knots.…”
Section: Size Effects Of Compression Strength and Modulimentioning
confidence: 78%
See 4 more Smart Citations
“…The size effect of the cross-sectional area on the compressive strength f c,0 was very small. We have reported that there is no size effect in the f c,0 of the solid timber specimens [7]. The main reason of the strength reduction may be related to knots because the solid timber specimens did not have knots, whereas all the glulam specimens excluding the 2.5-1 specimens had knots.…”
Section: Size Effects Of Compression Strength and Modulimentioning
confidence: 78%
“…(2) Cedar (H = mm) [7] Cedar (H = mm) [7] Cedar (H = mm) [7] Fig. 8 Influence of heights and widths of cross-sectional area on values of E L,f Fig.…”
Section: Size Effects Of Compression Strength and Modulimentioning
confidence: 99%
See 3 more Smart Citations